Climate Scenarios and Analogues for designing adaptation strategies in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CCAFS EA organized a followup training workshop for selected professionals from agricultural research organizations, line ministries and policy institutions in Kenya in November 2013.